Hubungan Pengetahuan Suami dengan Pemeriksaan Antenatal Care K4 di Puskesmas Danau Marsabut Kabupaten Tapanuli Selatan Tahun 2019 - ., Sriyanti; Sari, Novita (Universitas Aufa Royhan, 2019)
Antenatal Care is a planned program in the form of observation, education and medical treatment in pregnant women to obtain a process of pregnancy and childbirth that is safe and satisfactory. The type of descriptive correlative research with cross sectional approach with the aim to know the relationship of husband's knowledge with antenatal care K4 examination in Marsabut Lake Public Health Center of South Tapanuli Regency 2019. Data collecting tool used is questionnaire. The number of samples in this study were 33 people. The result of this research indicated that the majority of husbands knowledge about antenatal care examination was in sufficient category, 16 respondents (48.5%) and husband's knowledge minority about antenatal care were in good category (8) (24.2%). The majority of husbands brought their wife to do antenatal care, 19 respondents (57.5%) and husband's minority did not bring their wife to do antenatal care as many as 14 respondents (42.5%). There is a significant correlation between husband's knowledge with the action of antenatal care of K4 at Marsabut Lake Public Health Center of South Tapanuli Regency 2019, Kolmogorov-Smirnov test result obtained p value = 0.002 (p <0.05). Suggested to health personnel of Marsabut Lake Public Health Center to conduct counseling about antenatal care to husband of pregnant mother in order to increase husband knowledge about antenatal care. To the husbands to bring their wife to visit antenatal care check in order to avoid pregnancy disorder and to keep physical physical preparedness before delivery.